Construction of Brand Identity through Language in the Video Advertisements of Pakistani Telecom Companies - Sohaib Ul Hassan; Hammad Mushtaq (NUST Journal of Social Sciences and Humanities, 2021)
This research explored the construction of brand identity in the video advertisements of Pakistani telecom companies. Brand identity is constructed mainly by showing competitor’s submissive and weaker image rather than by using creative and unique advertising techniques. Data for this research was collected from five advertisements of five telecom companies. Positioning theory was applied on these advertisements. The data showed that all cellular companies of Pakistan were using positioning techniques to make their advertisements and construct the language of their ads to communicate with the society at large. The cellular companies have engaged in such kind of social communication due to the competition in the market of cellular services. This type of positioning in the language of advertisements is helpful in the conflicting and competitive business environment and explicitly or implicitly promotes competition. The research found that the cellular companies are using second order acknowledgement status and putting competitors in the third order status in their advertisements. The study found that Ufone is the company using this language technique mostly in its advertisements.